Red Glow : Yugoslav Partisan Photography and Social Movement, 1941-1945 - Konjikušić, Davor; Horvatinčić, Sanja; Klasić, Hrvoje (2022)
Davor Konjikušić offers an in-depth presentation and contextualization of the photographs created by Yugoslav partisans between 1941 and 1945. The book goes beyond an aesthetic depiction of the photographs; it also deals with the history of their use and function within one of the biggest anti-fascist movements in Europe during the Second World War. The photographs are used to trace the development of a movement that-while seemingly doomed to certain failure-nevertheless survived the most destructive war in human history. This book provides new answers to the question of photography's role as a medium and its significance and use in social movements.